Literature Review: Manfaat Intervensi Home Visit oleh Tenaga Kesehatan Terhadap Pencegahan Stunting - Nadifa, Shallu Afdha; Sutarto, Sutarto; Kusumaningtyas, Intan (Medula, 2024)
Stunting is a condition of children with a type of short stature caused by chronic malnutrition which is related to low socio-economic conditions, lack of nutritional intake, poor maternal health, a history of recurrent illnesses, and child feeding practices that do not meet standards. Stunting can be prevented through optimizing nutrition and health, namely home visit nutritional interventions by health workers. Home visits by health workers or trained cadres carried out during pregnancy or after the baby is born aim to educate parents directly and intensely. A review of the journal is necessary to find out the benefits of home visit interventions in reducing stunting so that the stunting problem in Indonesia can be resolved in an effective way. The method used in this research, the Systemic Literature Review (SLR), comes from national journals and international journals regarding the benefits of home visit interventions in the 2014-2024 time period. The results obtained from this study are that home visits can effectively increase mothers' knowledge and health behavior in caring for their babies and increase fathers' confidence in caring for children. Furthermore, due to the provision of correct parenting practices from health workers to families, home visits have been proven to be able to prevent stunting, increase weight gain, height, and child development scores, be able to increase the average IQ (Intelligence Quotient) score, children's executive function, and make children have higher pre-academic skills.